Implementation of a Strengths-Based Approach to Teaching in an Elementary School - Keith Brownlee; Edward Peter Rawana; Julia MacArtthur (University of Windsor, 2012)
Schools play a significant role in addressing children's mental health needs and this article contends that schools can further contribute to student mental well-being by adopting a strengths perspective model. A specific strengths assessment and treatment model is presented that extends to individual, peer and group interventions as well as discussions within the classroom that is applicable to every student in the school and not only students considered 'at risk'. By engaging an entire class, or indeed an entire school, in a dialogue of strengths, the concept of strengths can become a part of the culture of the school and lead to a positive school environment. This article provides an overview of the model, its implementation in a school, including the theory informing the interventions, followed by two brief case studies showing how the model was applied in a classroom. The intervention not only transforms the way in which educators interact with students, but it changes the way students perceive themselves and the manner in which they perceive their own potential.